The Impact of Campus Soundscape on Enhancing Student Emotional Well-Being: A Case Study of Fuzhou University - Qing Liang; Shucan Lin; Linwei Wang; Fanghuan Yang; Yanqun Yang (Buildings)
As the primary setting for students’ daily life and learning, university campuses are facing a growing concern about the impact of increased stress on students’ emotional well-being. The sound environment plays a critical role in affecting students’ mental health, learning efficiency, and overall well-being. However, research on the influence of campus soundscapes on students’ emotions is limited, and the mechanisms behind these effects remain to be explored. This study, using the Qishan Campus of Fuzhou University as a case, investigates the impact of campus soundscapes on students’ emotional perception and restorative effects. Four typical functional areas (academic zone (ACZ), residential zone (RDZ), recreational zone (RCZ), and administrative zone (ADZ)) were selected to analyze the effects of natural and artificial sounds on students’ emotions and physiological states. Based on EEG, eye tracking, sound level measurements, and questionnaire surveys, a one-way repeated measures ANOVA was used to assess students’ emotional arousal, valence, and physiological restoration under different soundscape conditions. The results showed that natural sounds, such as the sound of wind-blown leaves and flowing water, significantly improved students’ emotions and restorative effects, while artificial noises like construction sounds and traffic noise had negative impacts. Additionally, subjective perceptions of soundscape restoration were positively correlated with arousal, valence, and acoustic comfort, and negatively correlated with gaze frequency and pupil size. The findings provide a theoretical foundation for optimizing campus soundscape design and highlight the importance of natural sounds in enhancing students’ mental health and academic environment.